Penyediaan tanah untuk pembangunan rumah susun sederhana sewa di Surakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Abstract This research is aimed to know the base decision to choose the land of trace grave in Begalon, Panularan, Laweyan, Surakarta as the location of the development of these simple rent flat, the process of the served land, and the preparation in the way of arranging and managing these simple rent flat, also to know the view of the villagers around the trace grave with the policy taken by Surakarta local government. The used data are primary and secundary data. The primary data use trough field research by means of data collecting in the form of interview and questionaire. The secundary data use library research. The analysis is done by descriptive-qualitative methods and the conclusion use deductive methods. The result of the research presents, the base of decision of the choosing of the location of the simple rent flat is SK Walikota Surakarta No. 648. 1/ 37/ 1/ 2001, April, 15 th 2003 contenting the decision of the location of the development of the simple rent flat in the Begalon, Panularan, Laweyan, Surakarta. The prosess of the land serving is done by the government by give the money to the people who lives at that the land of trace grave before. The Surakarta's local government have been trying to construct a local decision related to the simple rent flat. The management of the simple rent flat, will be handed by DPU ofSurakarta local government Sub Dinas Cipta Karya of Settlement and Rent section. The member of society around the land of trace grave, that is the villagers of RT 05 RW 03 Begalon, states that they are agree to the policy taken by the Surakarta local goverment, by these reason as follows : 1) for the order of the land use by the owner